ORGANIZATION OF TRAINING BASED ON THE DESIGN METHOD REQUIREMENTS FOR THE TEACHER - Gulkhayo Oybekovna Akbarova (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the requirements for the teacher in the organization of teaching based on the lesson design method, the theory of the pedagogue’s teaching activity, the goal set for him, the elements of the lesson plan, the activities that the students should master, and at the same time, what the students will learn, what kind of work they will be able to do as a result are scientifically and pedagogically analyzed.